1994
DOI: 10.1515/bchm3.1994.375.1.53
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin and Ubiquitination in Cells from the Marine SpongeGeodia cydonium

Abstract: Marine sponges, e.g. Geodia cydonium, have been intensively used to investigate the biochemical and molecular biological basis of cell-cell- and cell-matrix adhesion. It has been shown that a family of galactose-specific lectins, which are present in the extracellular space of G. cydonium, is a main component involved in cell-matrix adhesion in the sponge system. In the present study it is outlined that the purified 16-kDa lectin-1 binds to a 67-kDa membrane-associated protein. This lectin-binding protein unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

1998
1998
2009
2009

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 14 publications
0
4
0
2
Order By: Relevance
“…The two NF-B-inhibiting marine natural products macrolide bryostatin 1 isolated from a bryozoan [56] and salinosporamide A isolated from a bacterium [24] are currently in clinical trials [58]. Several ecological reasons why marine natural products may inhibit NF-B have been established [20,21,[59][60][61][62][63][64][65][66][67][68][69].…”
Section: Discussionmentioning
confidence: 99%
“…The two NF-B-inhibiting marine natural products macrolide bryostatin 1 isolated from a bryozoan [56] and salinosporamide A isolated from a bacterium [24] are currently in clinical trials [58]. Several ecological reasons why marine natural products may inhibit NF-B have been established [20,21,[59][60][61][62][63][64][65][66][67][68][69].…”
Section: Discussionmentioning
confidence: 99%
“…Müller et al [184] observed that after the addition of purified AF to primary G. cydonium cell aggregates, DNA, RNA, and protein synthesis increased, and that the cells exhibited a high mitotic activity. Transcription of polyubiquitin mRNA was greatly increased when the dissociated cells were incubated with AF [185,186]. Binding of AF to the cells triggered protein phosphorylation [187] and ras gene expression [188,189].…”
Section: Involvement Of Spongicans In Signal Transduction Processesmentioning
confidence: 99%
“…The addition of purified AF to primary cell aggregates of the marine sponge Geodia cydonium resulted in increased DNA, RNA, and protein synthesis, as well as in a higher mitotic activity (Mü ller et al, 1976(Mü ller et al, , 1994Pfeifer et al, 1993). Binding of AF to the cells also triggered protein phosphorylation (Rottmann et al, 1987) and ras gene expression (Schröder et al, 1988).…”
Section: Introductionmentioning
confidence: 99%